Estrategias metodológicas para fortalecer el rendimiento académico del bloque curricular de relaciones y funciones, en los estudiantes de octavo año de educación general básica, de la unidad educativa anexa a la UNL, de la ciudad de Loja, período 2012 – 2013 - Chamba Yanangómez, Irma Patricia (2014)
The present study investigation is denominated “Methodological strategies to strengthen the academic yield of the curricular block of relationships and functions, in the student’s eighth years old, de la Unidad Educativa Experimental Anexa a la UNL, of the city de loja, period 2012-2013. The objectives that guided this research are: To investigate how the methods used by teachers affect the academic performance of Curricular Relations and Functions block of our eighth year basic general education. Establish how the techniques used by teachers affect the academic performance of block Curricular Relations and Functions, in our eighth year of basic general education. In developing the research work the importance of using appropriate them that contribute to quality Education, teachers must know the advantages they provide in their academic work allowing improve academic performance specifically in the Curriculum Block methodological strategies is determined Relations and functions. This required the use of methods such as the hypothetical deductive-inductive method, the, statistical and bibliographic method, as well as techniques such as; documentary collection, the survey. The instrument applied was a questionnaire that was sequences, according to the schedule established for the development of the planned activities which allowed the systematization and analysis of results. The main results are: In teaching inductive and deductive methods are those traditionally used in teaching. Teachers present concepts, principles, statements or laws, since the inductive method is the ideal way to achieve these principles, comparative analogous method is very important because it will help students to reason, to obtain new knowledge to help improve the academic performance. The use of each of the techniques by teachers is satisfactory for the teaching of mathematics, and performing activities such as exhibitions, research, group work so that the teaching is adequate to strengthen student learning. The knowledge acquired by students are rote therefore becomes a repetitive and rote learning that cause retention of knowledge and new information not related to the existing one, which this knowledge in isolation have not the same contribute to future learning rather hinder it.